The Influence of Quality of Service and Cost on Parents' Decisions to Choose Islamic Boarding Schools - Salimah, Salimah; Ruski, Ruski (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study was conducted to determine the impact of service quality and cost on parents' decision to enroll their children in pesantren. As part of this investigation, service quality and Cost were considered independent factors, while parents' decisions were dependent variables. The participants in this study consisted of two hundred parents of students who are still attending boarding schools in the 2022/2023 academic year. Meanwhile, the sample for this study consisted of fifty people who participated in the survey. The sampling method used was a probability sampling approach, precisely a simple random sampling method. This means fifty community members were equally likely to be selected as sample members. Questionnaires and documentation were the methods used for the data collection process. The analysis methods used were. This study uses several different analytical methods, including validity tests, reliability tests, multiple linear regression tests, and hypothesis testing. From this study, it is known that Quality of Service and Cost affect the variable Parents' Decision to Choose Islamic Boarding School because the Quality of Service and Cost variables show a positive influence, with a calculated t value of 3.085> t table of 0.2732, then Ho  is rejected and Ha is accepted. This means that the quality of service indicator positively affects the parents' decision (Y). Furthermore, the calculated t value equals l3.208> t table 0.2732, then Ho is rejected, and Ha is accepted. This means the cost indicator positively influences parents' decisions (Y).